2014
DOI: 10.1161/atvbaha.114.303718
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Circulating Lipocalin-2 Levels Independently Predict Incident Cardiovascular Events in Men in a Population-Based Cohort

Abstract: Objective-Adipose tissue inflammation and perturbation of adipokine secretion may contribute to the pathogenesis of cardiovascular diseases (CVD). Lipocalin-2 (LCN2), mainly released from adipocytes, has been shown to be positively associated with CVD in cross-sectional studies. We aimed to evaluate the association of LCN2 with CVD involving a population-based cohort recruited from the Shanghai Diabetes Study. Approach and Results-Serum LCN2 levels were measured using ELISA. Independent predictors of CVD devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…[26][27][28][29] Moreover, elevated circulating NGAL concentrations predict adverse cardiovascular events in patients. 29,30 We and others, have previously showed that Lcn2/NGAL is a direct target gene of the aldosterone/MR signaling pathway in the cardiovascular system. 5,31,32 The aim of this study was to analyze whether Lcn2/NGAL is a key actor of mineralocorticoid action in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 95%
“…[26][27][28][29] Moreover, elevated circulating NGAL concentrations predict adverse cardiovascular events in patients. 29,30 We and others, have previously showed that Lcn2/NGAL is a direct target gene of the aldosterone/MR signaling pathway in the cardiovascular system. 5,31,32 The aim of this study was to analyze whether Lcn2/NGAL is a key actor of mineralocorticoid action in the cardiovascular system.…”
Section: Discussionmentioning
confidence: 95%
“…It also accumulates in the renal cortical tubules and blood vessels [32]. As mentioned above, recent studies have shown positive correlations between serum NGAL levels and the risk of obesity, MetS, diabetes, and CVD [13][14][15][16]. According to Wang et al, NGAL levels are positively correlated with adiposity indexes such as BMI, waist circumference, and body fat percentage [13].…”
Section: Figmentioning
confidence: 97%
“…Body weight and height were measured in the morning, with participants lightly clothed and without Recent studies have suggested that serum levels of neutrophil gelatinase-associated lipocalin (NGAL) are associated with obesity, MetS, diabetes, and CVD [13][14][15][16]. NGAL, also known as lipocalin-2 or growth factor-stimulated superinducible protein 24, is a 25 kDa secretory glycoprotein [17] that was first identified as a protein secreted from human neutrophils [18].…”
Section: Anthropometric Parameters Blood Pressure and Blood Collectionmentioning
confidence: 99%
“…[4,7,15] Another prospective study indicated that the serum LCN2 concentration is a more effective early biomarker for predicting CVD events than the traditional inflammatory marker C-reactive protein (CRP). [5] …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in men, but not in women, serum LCN2 levels were found to be associated with obesity and obesity-related metabolic disorders. [4,5] Therefore, the present study was designed to investigate the associations of serum LCN2 levels with total body fat content and abdominal fat distribution in Chinese men, using bioelectrical impedance analysis to evaluate total body composition and abdominal MRI to measure visceral fat area (VFA) and subcutaneous fat area (SFA).…”
Section: Introductionmentioning
confidence: 99%